Perlukah Kesehatan Mental Remaja? Menyelisik Peranan Regulasi Emosi dan Dukungan Sosial Teman Sebaya Dalam Diri Remaja - Taufik Akbar Rizqi Yunanto (Universitas Andalas, 2018)
. Mental health is an important issue related to adolescent in their life. One of activitiy done by adolescent to spend their free time both at home and at school is to play with friends. In addition, friends factor becomes one of the strengthening factors in adolescent mental health. This study aims to determine the role of emotional regulation and peers social support toward mental health. This research was conducted on 102 students from Senior High School Yogyakarta, varying from 15 – 18 years old. Data was collected using teacher’s role interview, teacher’s role questionnaire, Mental Health Scale (Y), Emotional Regulation (X1) scale, and Peers Social Support (X2) scale. Data was analyzed using Anova and multiple regression analysis. The results showed that there was a strong relationship (F = 66,628; p < 0,01) between emotional regulation and peers social support toward mental health. Based on the analysis of determination, obtained R2 of 0,574 or 57,4%. This shows that the percentage of contributions, both independent to dependent variables is equal to 57,4%. Further analysis is needed to find out the impact of emotional regulation and peers social support in improving mental health literacy.